2021
DOI: 10.1007/s13562-021-00712-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of near isogenic lines for grain softness through marker assisted backcross breeding in wheat

Abstract: The genes for grain softness and rust resistance were transferred from a soft grained Australian wheat variety (Barham) to a hard grained Indian wheat variety (DBW14) through marker assisted back cross breeding. Backcrosses were made with recurrent parent in the BC 1 F 1 plants that were found positive for markers of Pina-D1a, Pina-D1b and Lr37b genes. The BC 2 F 1 plants were further screened and those that possessed the PinaD1a and Lr37b alleles were advanced up to BC 2 F 4 with continued marker assisted sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Marker assisted backcross breeding procedure was adopted to develop 16 derivatives (Near Isogenic Lines or NILs) which had the genes PinaD1aPinbD1a besides a leaf rust resistance gene Lr37b. The details of the breeding procedure can be found in Kumar et al (2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Marker assisted backcross breeding procedure was adopted to develop 16 derivatives (Near Isogenic Lines or NILs) which had the genes PinaD1aPinbD1a besides a leaf rust resistance gene Lr37b. The details of the breeding procedure can be found in Kumar et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The cookie snap test also confirmed the suitability of these NILs for confectionary purpose though NIL-2 appeared to be the best in this regard. All the NILs were evaluated for grain yield in the earlier study by us (Kumar et al 2021). The yield of NIL-13 is significantly lower than NIL-2 and 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the introgression study of transferring the 1Ay‐21 ∗ gene into commercial wheat cultivars is related to accelerated accumulation of grain protein content (GPC) and hence was suitable for bread‐making (Cao et al, 2021). A recent study reported the development of soft wheat lines suitable for biscuit making by introgression of grain softness gene pina‐D1a utilizing MAS into the Indian DBW14 wheat variety (Kumar et al, 2021; Rai et al, 2019). Y. Zhang et al (2016) and Singh et al (2014) explored the transcriptome in a single genotype that was suitable for making chapattis.…”
Section: Recent Molecular Approaches To Improve Wheat Grain Qualitymentioning
confidence: 99%